Independent Infinitive as the Subject of Linguodidactic Study - Matevosyan, Lianna (Bulletin of Yerevan University H: Russian Philology, 2025)
Linguists’ interest in the indefinite form of the verb remains undiminished – this topic is still relevant today. Linguists continue to debate its functional use. The syntactic multi functionality of the independent infinitive and the resulting disagreements among linguists give rise to disputes when differentiating between impersonal and infinitive sentences. Interest in the semantics of infinitive sentences – which are diverse, multifaceted, and thus open to an expanding list of semantic groups within the system of infinitive sentences and their descriptions – doesn’t fade away. The focus of our study is the independent infinitive, which functions as the principal element in infinitive sentences. However, it is presented as a constituent of the predicative basis of impersonal sentences alongside with the dependent infinitive in all Russian and domestic school textbooks, except for the textbook by V. V. Babaitseva and L. D. Chesnokova [2023]. This is true for the so-called “school grammar”, but the “university grammar” is altogether different. The combination of infinitive sentences with impersonal ones in “school grammar” is not accidental. Indeed, they have a common syntactic feature – non-subjectivity, the incompatibility of the main infinitive member with the nominative case. However, infinitive sentences differ significantly from impersonal ones. The infinitive is a non-predicative form, but in an independent syntactic position, it becomes a carrier of predicativity, i.e., it acquires the predicative meanings of objective modality. At present, in “school grammar”, the issue of distinguishing infinitive sentences as an independent type in the system of single-component sentences has not been resolved.